Electrically Driven Reversible Phase Changes in Layered In2Se3 Crystalline Film - Choi, Min Sup; Cheong, Byung-ki; Ra, Chang Ho; Lee, Suyoun; Bae, Jee-Hwan; Lee, Sungwoo; Lee, Gun-Do; Yang, Cheol-Woong; Hone, James; Yoo, Won Jong (WILEY-V C H VERLAG GMBH, 2017)
An unconventional phase-change memory (PCM) made of In2Se3, which utilizes reversible phase changes between a low-resistance crystalline phase and a high-resistance crystalline gamma phase is reported for the first time. Using a PCM with a layered crystalline film exfoliated from In2Se3 crystals on a graphene bottom electrode, it is shown that SET/RESET programmed states form via the formation/annihilation of periodic van der Waals' (vdW) gaps (i.e., virtual vacancy layers) in the stack of atomic layers and the concurrent reconfiguration of In and Se atoms across the layers. From density functional theory calculations, beta and gamma phases, characterized by octahedral bonding with vdW gaps and tetrahedral bonding without vdW gaps, respectively, are shown to have energy bandgap value of 0.78 and 1.86 eV, consistent with a metal-to-insulator transition accompanying the beta-to-gamma phase change. The monolithic In2Se3 layered film reported here provides a novel means to achieving a PCM based on melting-free, low-entropy phase changes in contrast with the GeTe-Sb2Te3 superlattice film adopted in interfacial phase-change memory.
Keywords: CHANGE MEMORY; BAND-STRUCTURE; TRANSITIONS; METAL; TRANSFORMATION; GAMMA-IN2SE3